2-Pyridyl glycoside: an alternative glycosyl donor in preactivation protocol. Issue 1 (1st January 2015) - Xiong, De-Cai; Yang, An-Qi; Yu, Yang; Ye, Xin-Shan
Graphical abstract: Abstract: 2-Pyridyl glycosides have been identified to be powerful glycosyl donors for the preactivation-based oligosaccharide synthesis. By using stoichiometric amount of Tf2 O, the 2-pyridyl glycosides were pre-activated, which subsequently underwent glycosylation reactions smoothly to produce the coupled products in high yields. Furthermore, the 2-pyridyl glycosides were applied to the efficient oligosaccharide assembly by the preactivation-based one-pot oligosaccharide synthesis protocol.